Hubungan Perhatian Orang Tua dan Motivasi Belajar dengan Keaktifan Belajar Siswa SD Negeri 22 Jeppe’e Kecamatan Tanete Riattang Barat Kabupaten Bone - Ilham; Arismunandar; Muhammad Irfan (PT PUSTAKA CENDEKIA GROUP, 2025)
The formulation of the problem in this study is how is the picture of parental attention, learning motivation, learning activity of UPT SD Negeri 22 Jeppe'e, Tanete Riattang Barat District, Bone Regency? and is there a significant relationship between parental attention and learning motivation with learning activity of UPT SD Negeri 22 Jeppe'e, Tanete Riattang Barat District, Bone Regency? This study is a correlation study that aims to determine the picture of parental attention, learning motivation, learning activity and the relationship between parental attention and learning motivation with learning activity of UPT SD Negeri 22 Jeppe'e, Tanete Riattang Barat District, Bone Regency. The research approach is a quantitative approach. Research data were obtained through questionnaires and documentation. The population in the study was all students of the upper class at UPT SD Negeri 22 Jeppe'e, Tanete Riattang Barat sub-district, Bone regency, totaling 54 students. The sample in the study was 54 students. The data analysis technique was descriptive and inferential statistical analysis. The results obtained in this study are a description of parental attention showing a very high category and learning motivation showing a very high category with learning activity showing a high category and parental attention and learning motivation having a significant relationship to student learning activity, especially in the upper class of UPT SD Negeri 22 Jeppe'e, Tanete Riattang Barat sub-district, Bone regency.